Using pseudo-AI submissions for detecting AI-generated code - Bashir, Shariq (Frontiers in computer science (Lausanne), 2025)
IntroductionGenerative AI tools can produce programming code that looks very similar to human-written code, which creates challenges in programming education. Students may use these tools inappropriately for their programming assignments, and there currently are not reliable methods to detect AI-generated code. It is important to address this issue to protect academic integrity while allowing the constructive use of AI tools. Previous studies have explored ways to detect AI-generated text, such as analyzing structural differences, embedding watermarks, examining specific features, or using fine-tuned language models. However, certain techniques, like prompt engineering, can make AI-generated code harder to identify.MethodsTo tackle this problem, this article suggests a new approach for instructors to handle programming assignment integrity. The idea is for instructors to use generative AI tools themselves to create example AI-generated submissions (pseudo-AI submissions) for each task. These pseudo-AI submissions, shared along with the task instructions, act as reference solutions for students. In the presence of pseudo-AI submissions, students are made aware that submissions resembling these examples are easily identifiable and will likely be flagged for lack of originality. On one side, this transparency removes the perceived advantage of using generative AI tools to complete assignments, as their output would closely match the provided examples, making it obvious to instructors. On the other side, the presence of these pseudo-AI submissions reinforces the expectation for students to produce unique and personalized work, motivating them to engage more deeply with the material and rely on their own problem-solving skills.ResultsA user study indicates that this method can detect AI-generated code with over 96% accuracy.DiscussionThe analysis of results shows that pseudo-AI submissions created using AI tools do not closely resemble student-written code, suggesting that the framework does not hinder students from writing their own unique solutions. Differences in areas such as expression assignments, use of language features, readability, efficiency, conciseness, and clean coding practices further distinguish pseudo-AI submissions from student work.